Concomitant downregulation of the imprinted genes DLK1 and MEG3 at 14q32.2 by epigenetic mechanisms in urothelial carcinoma - Greife, Annemarie (Clin Epigenetics, 2014)
BACKGROUND: The two oppositely imprinted and expressed genes, DLK1 and MEG3, are located in the same gene cluster at 14q32. Previous studies in bladder cancer have suggested that tumor suppressor genes are located in this region, but these have not been identified. RESULTS: We observed that both DLK1 and MEG3 are frequently silenced in urothelial cancer tissues and cell lines. The concomitant downregulation of the two genes is difficult to explain by known mechanisms for inactivating imprinted genes, namely deletion of active alleles or epitype switching. Indeed, quantitative PCR revealed more frequent copy number gains than losses in the gene cluster that were, moreover, consistent within each sample, excluding gene losses as the cause of downregulation. Instead, we observed distinctive epigenetic alterations at the three regions controlling DLK1 and MEG3 expression, namely the DLK1 promoter; the intergenic (IG) and MEG3 differentially methylated regions (DMRs). Bisulfite sequencing and pyrosequencing revealed novel patterns of DNA methylation in tumor cells, which were distinct from that of either paternal allele. Furthermore, chromatin immunoprecipitation demonstrated loss of active and gain of repressive histone modifications at all regulatory sequences. CONCLUSIONS: Our data support the idea that the main cause of the prevalent downregulation of DLK1 and MEG3 in urothelial carcinoma is epigenetic silencing across the 14q32 imprinted gene cluster, resulting in the unusual concomitant inactivation of oppositely expressed and imprinted genes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1868-7083-6-29) contains supplementary material, which is available to authorized users.